Biogenic Metallic Nanoparticles from Seed Extracts: Characteristics, Properties, and Applications. (14th October 2022) - Bhardwaj, Kanchan; Chopra, Chirag; Bhardwaj, Prerna; Dhanjal, Daljeet Singh; Singh, Reena; Najda, Agnieszka; Cruz-Martins, Natalia; Singh, Shubhangi; Sharma, Rohit; Kuča, Kamil; Manickam, Sivakumar
Abstract : Metal nanoparticles (MNPs) are popular in different research fields due to their unique physical and chemical properties and superior antimicrobial, anticancer, antioxidant, larvicidal, and catalytic potentials. Although conventional wet methods like colloidal synthesis, calcination, and spark ablation for synthesizing MNPs are effective, their synthesis uses an array of reducing and stabilizing agents and gases, making the process tedious. Additionally, metal nanoparticles induce oxidative stress through reactive oxygen species (ROS), showing high toxicity. Research and development in green chemistry have gained momentum and massive attention because of being efficient, clean, economical, environment-friendly, and free of hazardous byproducts. Recently, seed extracts in-lieu of chemical stabilizers and reducing agents have become popular because of the single-step green synthesis of MNPs. Seeds provide the researchers with a cost-effective alternate to other biological methods due to low maintenance costs, culture/growth independence for biomass, and diversity of phytochemicals as reducing and capping agents. Thus, effective green synthesis approaches are considered sustainable for MNP synthesis. This review depicts the literature on the challenges associated with metal and metal oxide nanoparticles and discusses their synthesis using seed extracts. The application section of the review discusses the antimicrobial, anticancer, and larvicidal activities of seed extracted-synthesized metallic nanoparticles. Furthermore, insights into the different biological potentials of the synthesized green MNPs have also been discussed.